Politicizing the social sciences: Islam and culture as socio-political fact - Mohd Yusof, Danial (Institute of Islamic Understanding Malaysia, 2008)
One possible way for a Muslim social scientist to respond and contextualize Islamic discourse is to mediate and cultivate a common perception and understanding between Muslim and non-Muslim readership through an understanding of Islam as a socio-political construct. In this paper, the discussion of Islam as socio-political fact is used to illustrate the impact of Western social sciences on the study of Islam. Through the appropriation of notions of transculture and the politics of identity, post-colonialism and post-modernism, the sociology of Islam is expanded as a paradigm through the understanding of strategic essentialism to deconstruct hegemonic terms of political discourse in academia